Pain reduction in fibromyalgia syndrome through pairing transcranial direct current stimulation and mindfulness meditation: A randomized, double-blinded, sham-controlled pilot clinical trial - Ramasawmy, Perianen; Khalid, Sarah; Petzke, Frank; Antal, Andrea (Frontiers in Medicine, 2022)
Background: This double-blinded, randomized and sham-controlled pilot clinical trial aimed to investigate the preliminary clinical efficacy and feasibility of combining mindfulness meditation (MM) and transcranial direct current stimulation (tDCS) for pain and associated symptoms in patients with fibromyalgia syndrome (FMS). Methods: Included FMS patients (age: 33 to 70) were randomized to three different groups to receive either ten daily sessions of anodal tDCS over the left primary motor cortex paired with MM for 20 min (active+MM, n=10), sham tDCS combined with MM (sham+MM, n=10) or no intervention (NoT, n=10). Patients in the bimodal therapy groups received a week of training in MM prior to the stimulation. Participants reported pain intensity, the primary outcome, by filling in a pain diary daily throughout the whole study. They were also evaluated for quality of life, pressure pain sensitivity, psychological wellbeing, sleep quality and sleep quantity. Assessments were performed at three time points (baseline, immediately after treatment and one-month follow-up). Results: Participants in the active+MM group did not exhibit reduced pain intensity following the bimodal therapy compared to controls. Patients in active group demonstrated clinically meaningful and significantly higher quality of life following the therapeutic intervention than other groups. There was no significant difference among groups regarding pressure pain sensitivity, sleep parameters and psychological scales. The combined treatment was well tolerated among participants, with no serious adverse effects. Conclusion: This study was the first to pair these two effective non-pharmacological therapies for pain management in FMS. In the light of an underpowered sample size, repetitive anodal tDCS combined with MM did not improve pain or FMS-associated symptoms. However, patients in the active+MM group reported higher quality of life than the control groups. Studies with more participants and longer follow-ups are required to confirm our findings. Clinical Trial Registration: [www.drks.de], identifier [DRKS00023490].